2022
DOI: 10.3390/ijerph19074313
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Problems and Polypharmacy in Nursing Home Residents: A Cross-Sectional Study

Abstract: At present, 19.2% of the Spanish population is aged 65 or older. Polypharmacy is a frequent condition among the elderly, especially in those living in nursing homes, which is associated with adverse outcomes, such as adverse drug events or drug-drug interactions. This study aimed to assess the pattern of polypharmacy in a nursing home in Leon, one of Spain’s most ageing regions, and its relationship with different drug-related problems. A descriptive, observational, and cross-sectional study design was used; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Benzodiazepines are commonly prescribed in the elderly for anxiety and insomnia in spite of being one of the pharmacological groups usually implicated in the occurrence of potential DDIs and adverse reactions (sedation, falls and fractures, mental confusion, cognitive decline, etc.) and in the prescription of unnecessary drugs [26,[50][51][52]. If the Beers criteria were applied, benzodiazepines were also involved in 21.6% of PIMs, a value very close to that obtained with the STOPP criteria without the A1 criterion.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Benzodiazepines are commonly prescribed in the elderly for anxiety and insomnia in spite of being one of the pharmacological groups usually implicated in the occurrence of potential DDIs and adverse reactions (sedation, falls and fractures, mental confusion, cognitive decline, etc.) and in the prescription of unnecessary drugs [26,[50][51][52]. If the Beers criteria were applied, benzodiazepines were also involved in 21.6% of PIMs, a value very close to that obtained with the STOPP criteria without the A1 criterion.…”
Section: Discussionmentioning
confidence: 64%
“…We also found that 37.2% were related to interactions detected in different sections of the Beers criteria: potentially clinically important DDIs to be avoided in older adults (23.3%) and PIM use in older adults due to drug-disease or drug-syndrome interactions that may exacerbate the disease or syndrome (13.9%). In the case of potentially clinically important DDIs, 87.5% were due to the use of three or more CNS-active drugs, and in most of them (83.1%), combinations including benzodiazepines and nonbenzodiazepines, benzodiazepine receptor agonist hypnotics, or opioids were included, with a remarkably increased risk of falls and other disorders such as central nervous system depression and dementia [26,50,59,60]. A high consumption of benzodiazepines has been reported among NH residents, who also showed an increased risk of mental health disorders [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…168 Also, progressive aging of the population is accompanied with multimorbidity and attendant multiple drug use can be problematic, especially if patients visit several specialists while the information on prescriptions is not exchanged. 149,150,[153][154][155] In addition, patients should also be aware of the importance of this topic and inform their general practitioner about their current use of different medications. Patient information campaigns, organized by health authorities, can increase patient awareness significantly.…”
Section: Discussionmentioning
confidence: 99%
“…151,152 In western countries, the increase in age of the population and the wider use of drugs for chronic diseases has increased the possibilities of liver-related drug-drug interactions. 149,150,[153][154][155] As described in the preceding sections, the levels of numerous metabolic enzymes and transporters are affected in liver disease. For example, it is well known that CYP3A4 levels are decreased in patients with liver cirrhosis, 136 and also in patients with diabetes and MASLD.…”
Section: Drug-drug Interactions In Liver Diseasementioning
confidence: 99%